Desain Ilustrasi Booklet Profesi Jamu Gendong Di Era Milenial - Diki, Diki; Kurniawan, Ivan (Fakultas Desain Universitas Komputer Indonesia, 2021)
Herbal medicine is one of the Javanese cultures that existed in ancient times during the Majapahit era. Along with the times of technological advances in terms of modes of transportation, now many herbal medicine sellers use vehicles and do not hold their herbs. The identity of the herbal medicine profession has also begun to shift from cultural values because it no longer uses kebaya and batik cloth. Through current convenience, the seller of herbal medicine is more looking at the economic and practical aspects. So, the problem is the millennial generation thinks that this is only a normal profession and does not have any cultural value. Plus the herbal medicine profession has begun to be scarce in some rural and urban areas; it is difficult for millennials to interact directly with this profession. Whereas carrying herbal medicine is one area of work that is quite helpful in the economy of some circles of society. So the design is important to do to provide information on the carrying herbal medicine profession for millennials. The booklet is a medium that will be used in the design to provide information on the existence of the carrying herbal medicine profession.